Properties of polymer concrete containing active micro filler of palm oil fuel ash - Nur Hafizah, A Khalid; Abdul Rahman, Mohd Sam; Azman, Mohamed; Nor Hasanah, Abdul Shukor Lim; Nur Farhayu, Ariffin (IOP Publishing, 2019)
This paper presents the mechanical properties of polymer concrete (PC) containing active-mobilize micro filler of palm oil fuel ash (POFA). As known fact, the wrong chosen of filler for PC will lead to give poor properties of PC. Inthis study, the POFA was divided into two types; ground POFA and unground POFA. The fine micro filler of ground POFA was compared with calcium carbonate. While, coarse micro filler of unground POFA was compared with silica sand. Before the micro fillers being to be utilized in PC, the micro fillers were characterized under microstructure examinations; particle size distribution and morphology. Then, the mechanical properties of PC with different micro fillers were investigated under compression, flexural, and splitting tensile test. Further test on the denseness of PCs were carried out under ultra-pulse velocity (UPV) test. From the results, it was found that the PC with ground POFA had superior mechanical properties as compared to others. In conclusion, the ground POFA had active micro filler which functioning to fill the gap and to provide the dense packed structure inPCs.